Quality Confirmed by Expert Evaluation: Laboratory Control of Medicinal Products in the System of Regulatory Procedures - E. A. Mamashina (Regulatory Research and Medicine Evaluation, 2026)
In this interview, E.A. Mamashina, Deputy Head of the Testing Centre for Medicinal Products Quality Control, discusses the objectives and tasks of laboratory quality expertise within the framework of registration procedures and the introduction of medicinal products onto the market. Data on the activities of the Testing Centre for Medicinal Products Quality Control in 2025 are presented (1702 assignments, 2140 medicinal product names; a 22% increase in the volume of products released onto the market). The impact of the transition to Eurasian Economic Union (EAEU) regulations (98% of assignments under the Union), sanctions-related and logistical challenges faced by applicants, and regulatory mechanisms for overcoming them, including remote testing, are discussed. Special attention is given to pre-registration services provided by the Scientific Centre for Expert Evaluation of Medicinal Products: the procedure for preliminary sample calculation (60% increase in requests in the first half of 2026), method development and validation, stability studies, raw material control, and training workshops.